Ripening process study in persimmon (D. kaki) fruits on tree focused in ethylene - Blasco, Manuel; Gil-Muñoz, Francisco; Badenes, María L. (ISHS, 2022)
Fruit ripening is a highly coordinated, genetically programmed and an irreversible phenomenon involving a series of physiological, biochemical and organoleptic changes that lead to the development of a soft and edible ripe fruit with desirable quality attributes. These changes are driven by a cascade of molecular events, starting with the activation of signaling pathways. In persimmon, as in other climacteric fruits, the plant growth regulator ethylene is the major signaling molecule that controls most aspects of fruit ripening. Ethylene biosynthesis is only induced when fruits are detached from the tree, and these levels of ethylene production are scarce, similar to those produced by non-climacteric fruits. Therefore, analysis of ethylene synthesis and reception pathways will provide information of fruit ripening process. The expression profile of genes involved in ethylene synthesis and response pathways related to ripening and fruit softening, from early stages of fruit development to over-ripening, were measured in fruits of four cultivars of persimmon differing in maturity dates and astringency type. Our study suggests that ethylene accumulation in persimmon fruits determines transition from System 1 to System 2. This information provides insight into the molecular mechanisms and a description of the gene network involved in persimmon fruit ripening, contributing to the genetic knowledge of this climacteric fruit. This knowledge would be useful for crop management and breeding programs aimed at expanding the harvest season.